Determination of optimum sample size for measuring the contributing characters of bottle gourd (Bangladesh Journal of Agricultural Research, 2016)
To improve efficiency in collecting data from field experiment on fruit attributes of bottle gourd (Lau), the sample size was studied for sample size at Olericulture Division, Horticulture Research Centre (HRC) of Bangladesh Agricultural Research Institute (BARI) Gazipur during 2012-13. The treatments/varieties were LS 0026-5-3, LS 0012-5-3, LS 117-F-1, LS 117-A-2 and BARI Lau-3. Fruit length, breadth and weight of bottle gourd (Lau) data were collected from the experimental plot. The data were used to design optimum sampling plan from equal number of observations per cell. The observation on fruit length (cm), breadth (cm) and weight (kg) were taken from 5 plots/treatments at random. A randomized complete block design (RCBD) with 3 replications and five treatments/varieties was used in this experiment. Five (5) plants per plot and 2 fruits per plants (10 fruits per plot) were the original sampling plan for this experiment. A sampling plan of selecting 4 plants at random and measuring 2 fruits per selected plant (8 fruits per plot and plots were 25m2 i.e. 10m long and 2.5m wide) was found to be optimum and economical for taking measurements of fruit attributes in field experiments on bottle gourd.Bangladesh J. Agril. Res. 40(4): 703-709, December 2015